PREPARING STUDENTS FOR INNOVATIVE ACTIVITIES IN PRACTICAL ART CLASSES (American Journal of Pedagogical and Educational Research, 2023)
This article discusses preparing students for innovative activities in practical art classes. Based on practical information, the author studied and analyzed the unique aspects of preparing students for innovative work in practical art classes based on existing scientific literature.